The first : how to think about hate speech, campus speech, religious speech, fake news, post-truth, and Donald Trump - Fish, Stanley Eugene (One Signal Publishers, Atria, 2019)
"From celebrated public intellectual and New York Times bestselling author, Stanley Fish, comes an urgent and sharply observed look at one of the most hotly debated issues of our time: freedom of speech"--